1980
DOI: 10.1002/eji.1830100904
|View full text |Cite
|
Sign up to set email alerts
|

Original H‐2d and alien H‐2k‐like antigens of a BALB/c fibrosarcoma as defined by in vitro and in vivo studies of cell‐mediated immunity

Abstract: The present study examines the immunosensitivity and the immunogenicity of both original H‐2d and alien H‐2k‐like antigens of the BALB/c (H‐2d) fibrosarcoma C‐1 as detected by in vitro and in vivo cell‐mediated cytotoxicity (CMC) assays. It was found that 51Cr‐labeled C‐1 cells were lysed in vitro by C 57 BL/6 anti‐H‐2d lymphocytes. The specificity of this reaction was shown by cold inhibition experiments in which the anti‐H‐2d cytotoxic activity on YC8 (H‐2d) targets was inhibited by unlabeled YC8 or C‐1 but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
1990
1990

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The cytotoxicity of in vitro stimulated lymphocytes was tested against tumor target cells in 4-or 18 h 51Cr-release assay, as previously described [13]. The cytotoxicity of in vitro stimulated lymphocytes was tested against tumor target cells in 4-or 18 h 51Cr-release assay, as previously described [13].…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity of in vitro stimulated lymphocytes was tested against tumor target cells in 4-or 18 h 51Cr-release assay, as previously described [13]. The cytotoxicity of in vitro stimulated lymphocytes was tested against tumor target cells in 4-or 18 h 51Cr-release assay, as previously described [13].…”
Section: Methodsmentioning
confidence: 99%
“…The assay was carried out as previously described [24]. Briefly, effectors and »lCrlabelled targets were added to triplicate U-bottom wells of 96-well microplates (Costar 3799) in a final volume of 200 l-tl and incubated at 37 ° C for 4 h. In cold-target inhibition studies, unlabelled competitor cells were added first, followed by »lCr-labelled targets and an appropriate number of effectors.…”
Section: Generation Of L a K Cellsmentioning
confidence: 99%
“…The outgrowth of otherwise lethal doses of the Moloney virusinduced lymphoma YC8 and of its clones was inhibited in BALBlc mice immune to DBAl2 (H-2'9, C3Hf (H-ZC), C3H.SW (H-Zb), C3H It has been reported that murine tumors may express alien histocompatibility antigens (HA) encoded both by the MHC or by non-H-2 genes (Parmiani et al, 1979). One approach used to detect cross-reactions between tumors and allogeneic normal cells was to see whether alloimmunization of recipient mice would generate in vivo resistance to subsequent challenges of syngeneic tumors or in vitro cytotoxic activity to tumor targets (Gipson et al, 1978;Fujiwara et al, 1978;Parmiani et al, 1980;Russell et al, 1979;Schinmacher et al, 1980;Sensi et al, 1980). Without identifying the cross-reaction antigens, Zarling et al (1978a) were able to elicit significant cell-mediated killing on human autologous neoplastic targets by peripheral blood lymphocytes of certain patients sensitized in vitro to a pool of 20 different allogeneic normal lymphocytes, a panel representative of the whole spectrum of HLA antigens or of their lymphocyte-defined determinants.…”
mentioning
confidence: 99%